Morphology and swimming performance - Kjendlie, P.-L.; Stallman, R. (World book of swimming: From science to performance, 2012)
This chapter deals with the way morphology influences performance and mechanics of swimming. Performance in swimming is influenced by size. A taller swimmer will generally swim faster. Larger propelling sizes better the propelling efficiency and lower the stroke rate - creating a more energy efficient mode of swimming. Drag is influenced by size: a taller swimmer will create less wave resistance at the same speed, and the tall swimmer will have a greater potential for maximal velocity due to a higher hull speed. Pressure drag is directly influenced by the projected cross sectional area which increases drag. During a swimming race, a taller swimmer will have a shorter true race distance due to turning and finishing actions with their center of mass further away from the pool wall.